Endometrial expression of receptivity markers subject to ovulation induction agents - Freis, Alexander; Germeyer, Ariane; Jauckus, Julia; Capp, Edison; Strowitzki, Thomas; Zorn, Markus; Machado Weber, Amanda (Archives of gynecology and obstetrics, 2019)
Implantation rates differ according to ovulation induction agents in ART. This study investigates the different local endometrial effects of LH- versus hCG-induced ovulation.